Politeness Strategies in Social Media: the Case of “Covid -19” Pandemic in Facebook and Twitter Posts - Alvin Zonatan Sagala; Sumarsih . Sumarsih; Isli Iriani Indiah Pane (LINGUISTIK TERAPAN, 2022)
This study deals with the types of politeness strategies on social media: Facebook posts and Twitter, according to Brown and Levinson's (1987) theory. This research is included in the type of descriptive qualitative research. To answer questions in the research, the author took 30 Facebook posts and Twitter data according to Creswell's (2009) theory, namely by downloading posts from Facebook and Twitter randomly with the theme of Covid-19. Then the data was condensed, displayed and verified conclusion drawn. The results of this study found that there were 5 types of positive politeness strategies and 6 negative politeness strategies. The positive sub strategies are: making offer, showing a sense of optimism, involving the interlocutor and speaker in a certain activities , giving and asking for reasons, and expector demand reciprocity. while the negative politeness strategies include: indirect expression), using fences, stating FTA as a general social, stating clearly that the speaker has given goodness.